The Suzaku view of highly-ionised outflows in AGN: I - Statistical detection and global absorber properties - Gofford, J; Reeves, J; Tombesi, F; Braito, V; Turner, T; Miller, L; Cappi, M (2012)
We present the results of a new spectroscopic study of Fe K-band absorption in Active Galactic Nuclei (AGN). Using data obtained from the Suzaku public archive we have performed a statistically driven blind search for Fe XXV Hea and/or Fe XXVI Lyb absorption lines in a large sample of 51 type 1.0-1.9 AGN. Through extensive Monte Carlo simulations we find statistically significant absorption is detected at E>6.7 keV in 20/51 sources at the P(MC)>95% level, which corresponds to ~40% of the total sample. In all cases, individual absorption lines are detected independently and simultaneously amongst the two (or three) available XIS detectors which confirms the robustness of the line detections. The most frequently observed outflow phenomenology consists of two discrete absorption troughs corresponding to Fe XXV Hea and Fe XXVI Lyb at a common velocity shift. From xstar fitting the mean column density and ionisation parameter for the Fe K absorption components are log(NH/cm^{-2})~23 and log(xi/erg cm s^{-1})~4.5, respectively. Measured outflow velocities span a continuous range from <1,500 km/s up to ~100,000 km/s, with mean and median values of ~0.1c and ~0.056c, respectively. The results of this work are consistent with those recently obtained using XMM-Newton and independently provides strong evidence for the existence of very highly-ionised circumnuclear material in a significant fraction of both radio-quiet and radio-loud AGN in the local universe.